Objective napping, cognitive decline and risk of cognitive impairment in older men - Leng, Yue (Alzheimers Dement, 2019)
INTRODUCTION: Little is known about the longitudinal association between napping and cognitive impairment in older adults. METHODS: We used wrist actigraphy to measure naps in 2751 community-dwelling older men. Cognition was assessed repeatedly over 12 years, and clinically significant cognitive impairment was determined by physician diagnosis, Alzheimer’s medication use or a significant cognitive decline. RESULTS: After adjustment for all covariates, men with longer napping duration had greater cognitive decline and higher risk of cognitive impairment. Men who napped for ≥120 min/day (vs. <30 min/day) were 66% more likely to develop cognitive impairment (OR=1.66, 95%CI: 1.09–2.54) in 12 years. Further adjustment for nighttime sleep quality did not appreciably alter the results. The association between napping and cognitive impairment was more pronounced among those with higher sleep efficiency and average sleep duration. DISCUSSION: Napping might be useful as an early marker of cognitive impairment in the elderly, and its cognitive effects may differ by nighttime sleep.